Hybrid Digital-Conventional Leadership Model and Its Influence on the Well-Being and Performance of the Academic Community - Pipin Sukandi; Neuneung Ratna Hayati; Vina Silviani Marinda (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The COVID-19 pandemic accelerated digital transformation in higher education, creating an urgent need for leaders who can effectively integrate digital technologies with conventional leadership approaches. However, many leaders still struggle to balance digital efficiency with relational effectiveness, which negatively affects the well-being and performance of the academic community. This study examines the effects of a hybrid leadership model, which combines digital and conventional leadership approaches, on the psychological well-being and performance of the academic community in Indonesian higher education institutions. In addition, the study investigates the mediating role of well-being in the relationship between leadership and performance. The study employed a sequential explanatory mixed-methods design. Quantitative data were collected from 200–300 respondents using stratified random sampling through validated instruments, including the MLQ-5X, PERMA Profiler, DASS-21, and the Individual Work Performance Questionnaire (IWPQ). Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) were used to test the proposed hypotheses. Furthermore, qualitative data were obtained through in-depth interviews and focus group discussions to enrich the interpretation of the quantitative findings. The results supported all four hypotheses. Hybrid leadership significantly and positively influenced both psychological well-being (H1) and academic performance (H2). Well-being also demonstrated a significant positive effect on performance (H3). Moreover, well-being partially mediated the relationship between hybrid leadership and performance (H4), indicating that leadership contributes to performance both directly and indirectly through the enhancement of well-being. Overall, the findings suggest that hybrid leadership effectively improves both well-being and performance in higher education institutions. Therefore, higher education leaders should develop dual competencies by strengthening digital fluency while maintaining authentic interpersonal leadership skills. In addition, institutions should integrate well-being initiatives into their performance management systems as a strategic component of sustainable organizational development.